Diet Supplementation With Sulfur Amino Acids Modulated Fermentation Metabolome and Gut Microbiome in Goats - Teklebrhan, Tsegay; Tan, Zhiliang (Frontiers in Microbiology, 2022)
Dietary amino acids shift hydrogen metabolism to alternative hydrogen sinks than methanogenesis and influenced microbial fermentation metabolites and microbiome associated with solid and liquid fractions in gut regions of goats. Goats were randomly assigned to one of four treatments, basal diet (control), control diet supplemented with Methionine (Met), control diet supplemented with Lysine (Lys), and control diet supplemented with methionine and lysine (ML). Goats were euthanized and gut region contents were used to determine dissolved gasses, volatile fatty acids (VFA), and microbial abundances. Goats fed Met alone or in combination had less (p < 0.05) acetate, acetate to propionate ratio, while greater propionate in the foregut and hindgut than those fed control or Lys. Nevertheless, increased branched-chain VFA (p < 0.05), was found in the foregut and hindgut of goats fed in the amino acid supplements than those in control. Goats fed ML had the highest (p < 0.01) ammonia nitrogen in both foregut and hindgut than those goats in other treatment groups. In addition, goats in amino acid supplements had higher (p < 0.01) ammonia nitrogen in both foregut and hindgut, with the highest in the former region, than those in control. Goats fed Met alone or in combination had less (p < 0.01) dH2, dCH4 while having increased dH2S both in the foregut and hindgut than control or Lys. Goats fed Met and Lys either alone or in combination had increased (p < 0.01)16S rRNA gene copies of total bacteria, methanogens, and 18S rRNA of protozoa, fungi, and. fiber utilizing bacterial species associated with solid vs. liquid both in the foregut and hindgut than those in control. This study suggests that sulfur-containing amino acids shift hydrogen to alternative hydrogen sink i.e., H2S over methanogenesis and modified gut fermentation metabolites, microbiota associated with solid and liquid both in the foregut and hindgut of goats.